From pixels to 3D worlds: Enhancing digital collaboration for distributed teams - Koustas, Spyridon Georg; Breimair, Georg; Amler, Michael Karlheinz (Procedia CIRP, 2024)
The rise in distributed and remote work arrangements has been substantial, with expectations of further expansion. Such a trend presents both opportunities and challenges, particularly with respect to digital collaboration. Available literature proposes that virtual interactions result in limited knowledge transfer and fewer creative ideas compared to physical spaces, due to the lack of shared physical space and limitations in facilitating nonverbal communication. To address these challenges, this paper takes a design-science research approach and presents a real-time communication and collaboration tool, that supports distributed teams in collaborating online. The tool incorporates playful features within a low-poly design that allow for the creation of 3D objects in a shared, virtual environment and enables interactions between users, ultimately fostering engagement and improving spatial knowledge representations. Combining 3D avatars with real-time audio, video, and text communication enhances the efficient transfer of knowledge and fosters interpersonal relationships. The artifact undergoes two iterations of evaluation, using user tests in combination with surveys, to ensure research rigor. Early findings demonstrate a considerable level of user engagement with the tool, which leads to enhanced communication and collaboration among users. Furthermore, it facilitates quick visualization of ideas and enhanced sharing of knowledge during user test
Keywords: Digital collaboration; virtual 3D environments; design education